2015
DOI: 10.3846/13923730.2014.893918
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Design of Hydraulic Lime-Based Grouts for Masonry Consolidation

Abstract: Grout is a concentrated suspension that can be employed for the homogenisation and consolidation of systems presenting pores, voids and cracks, such as inner core of old stone masonries. A grout should be well conceived, taking into account the optimisation of its performance; this means that simple binder and water formulations prove to be inadequate. Hence, the effect of different admixtures and pozzolans, which are traditionally used in concrete, on the fresh and hardened properties of hydraulic lime grouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Sonebi [100] demonstrated that the small size and spherical shape of fly ash particles increase the grout density and reduces the yield stress values due to the ball bearing effect between the binder particles, which reduces the friction forces and consequently reduces the shear stress needed to start the flow. Similar trends of higher fluidity in the presence of fly ash were observed by Baltazar et al [34].…”
Section: Fly Ashsupporting
confidence: 88%
See 1 more Smart Citation
“…Sonebi [100] demonstrated that the small size and spherical shape of fly ash particles increase the grout density and reduces the yield stress values due to the ball bearing effect between the binder particles, which reduces the friction forces and consequently reduces the shear stress needed to start the flow. Similar trends of higher fluidity in the presence of fly ash were observed by Baltazar et al [34].…”
Section: Fly Ashsupporting
confidence: 88%
“…The injection grouts are often referred to as non-Newtonian, thixotropic, and in possession of a yield stress [14,[34][35][36]. This non-Newtonian behavior can be attributed to mechanisms in which the shear stress orients the suspended binder particles in opposition to the randomizing effects of Brownian motion [14,[37][38][39].…”
Section: Rheological Modelsmentioning
confidence: 99%
“…From Table 9 it is clear that the NS dosage is the factor with the greatest influence on viscosity values. As reported elsewhere [15,30], the addition of particles with a high specific surface promotes a great influence in the rheological parameters, namely in the plastic viscosity. The introduction of small-sized particles as NS and SF is the source of additional surface area, resulting in an increase of contact forces among fine particles, leading to easier coagulation due to interparticle interactions (Van-der-Waal's interactions).…”
Section: Rheological Measurementsmentioning
confidence: 53%
“…However, these simple formulations are unable to perform efficient consolidation, therefore requiring the use of additional products. According to other studies [10][11][12][13][14][15][16], some grout properties can be improved with the use of additives in the grout composition, in particular pozzolans that can be added to the base grout. Even though the influence of incorporation of pozzolans as supplementary materials in grouts production has been investigated widely in the last two decades [10,[15][16][17][18][19], the influence of materials with a nano-size in grouts for old stone masonry consolidation has not been investigated to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…Rheological measurements allow the evaluation of the effects of different grout composition on the fresh behaviour and a proper characterization through rheological models [8]. Based on previous works [6,9] it is accepted that fresh behaviour of natural hydraulic lime grouts can be represented using the Bingham model. Therefore, if the fresh grout is assimilated to a Bingham fluid two independent parameters are needed to describe the rheological behaviour, such as yield stress and plastic viscosity.…”
Section: Introductionmentioning
confidence: 99%